Liquid-phase oxidation of hydroxylamine with ultrasonic irradiation - JANOWSKI, Andrzej; RZESZOTARSKA, Jadwiga (Archives of Acoustics, 1989)
The sonochemical oxidation of hydroxylamine in alkaline aqueous, aqueous-methanol and methanol solutions yielded peroxonitrite ion as a main product. A little nitrite and nitrate were also formed. The oxidation yield increased with methanol concentration in the solution. The mechanism of oxidation both in aqueous solution and in the presence of alcohol is discussed.